PENGARUH SOSIALISASI PAJAK, PEMAHAMAN PAJAK, KESADARAN PAJAK TERHADAP KEPATUHAN MEMBAYAR WAJIB PAJAK PP 46 TAHUN 2013 PADA PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KEBAYORAN BARU JAKARTA SELATAN - Meiliyah Ariani (LPPM UNIVERSITAS BINA INSAN, 2017)
This study aims to determine the influence of socialization, understanding taxes, tax awareness to compliance of taxpayers pay PP 46 Year 2013 on SMEs in Kebayoran Baru. Sample selection is done by using accidental sampling method. The research data was collected from taxpayers who pay taxes PP 46 Year 2013 On Perpetrators of SMEs in Kebayoran Baru. The samples used were 100 respondents. Data analysis technique used is multiple regression with SPSS version 21. The results showed that the factors of socialization taxes as measured by socializing direct and socialization indirectly, understanding taxes as measured by knowledge of the general provisions and procedures of taxation, knowledge of the tax system and knowledge of the function of taxation and awareness of tax measured by the tax is a form of participation , delay and a reduction in the tax burden, the tax is set by law and imposed a partial positive and significant impact on tax compliance in paying taxes PP 46 Year 2013 on SMEs in Kebayoran Baru Jakarta Selatan.